Marginal Structural Changes in Peri-zone of Shimla City (H.P.) - Devi, Divya; Singh, M. P. (National Geographical Journal of India, 2022)
This paper stresses the necessity to study the spatio-temporal change in the city of Shimla. Rapid changes in the landuse pattern of a region have become an important concern in these days. Land use changes produced by human and natural phenomena play a major role in global as well as at regional scale patterns of the earth system. Understanding the physical complexities of various scales, from individual buildings, plots, street blocks and the street patterns that make up the structure of towns helps us to understand the way in which town have grown and developed. The city is a dynamic organism, constantly in process of evolution. The evolution involves both a modification of long established functions and the addition of new functions. The urban sprawl or expansion often encroaches upon agricultural or productive forestland; neither of which can resist the momentum of urbanization. City growth is an indicator of development, the change in landuse pattern from rural to urban is monitored to estimate population, predict and plan direction of urban sprawl for developers. It resulted in the establishment of many new business centers and growth of existing ones. The Key element for mapping rural to urban land use change is the ability to discriminate between rural uses (farming, pasture, forest) and urban use (residential, commercial, recreational). In Shimla town many residential, industrial and transport centers, government offices, agencies, research and development institutes, educational centers, recreational facilities have sprung up. This has given fresh impetus to the overall development of the capital city